2015
DOI: 10.1007/s11162-015-9376-9
|View full text |Cite
|
Sign up to set email alerts
|

Managing Institutional Research Advancement: Implications from a University Faculty Time Allocation Study

Abstract: While much is known about faculty time allocation, we know very little about how traditional managerial factors influence faculty time allocation behaviors. We know even less about the possible downsides associated with relying on these traditional managerial factors. Using survey data from the National Science Foundation/Department of Energy Survey of Academic Researchers, our study predicts faculty time allocations to grant writing as a function of pressure from administrative superiors. We then examine how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…This logic is characterized at least in part by a clear organizational objective of profit maximization and development of strategies (i.e., marketing strategies) and organizational structures (i.e., sales or enrollment departments) to fulfill this objective. In this logic, managerialism is the dominant operational paradigm, and supervisor–subordinate relations are more meaningful than they are in traditional higher education (Anderson and Slade ). Many for‐profits have high‐pressure sales environments (see Coutts ; Kirkham ), and some of the most profitable for‐profit colleges spend more money on marketing than instruction on a per‐student basis (Stratford ).…”
Section: Public Value Theorymentioning
confidence: 99%
“…This logic is characterized at least in part by a clear organizational objective of profit maximization and development of strategies (i.e., marketing strategies) and organizational structures (i.e., sales or enrollment departments) to fulfill this objective. In this logic, managerialism is the dominant operational paradigm, and supervisor–subordinate relations are more meaningful than they are in traditional higher education (Anderson and Slade ). Many for‐profits have high‐pressure sales environments (see Coutts ; Kirkham ), and some of the most profitable for‐profit colleges spend more money on marketing than instruction on a per‐student basis (Stratford ).…”
Section: Public Value Theorymentioning
confidence: 99%
“…On the issue of initiation versus management, which we investigated in hypothesis 3, firm employees are relatively less likely to initiate collaborations than their university counterparts but they seem to generally take over management once the collaboration has been established. This can be attributed to differences in time horizons between university scientists (long-term) and firm employees (short-term) (Link et al, 2008;Libaers, 2012;Anderson and Slade, 2016;and, broadly, Juster and Stafford, 1991) as well as to differences in personality types (Erez and Shneorson, 1980). University scientists are interested in actually carrying out the research but they would rather avoid administration and management tasks of those projects (Grimpe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, they require creative structuring, as the clock speed of academic research and business practice can be wildly divergent. Conversely, many academics think long-term, and this can be an advantage for a business as it may overcome managers' tendency to look to the next quarter (Link et al, 2008;Libaers, 2012;Anderson and Slade, 2016;and, broadly, Juster and Stafford, 1991). "Going long" with academics in the search for new ideas can unlock a range of possibilities and even help to create a new innovation ecosystem that will sustain the business for longer periods of time into the future (O'Kane et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex challenges of university administrators to control allocation of time spent by university faculty members on their various work activities has been documented (Hull 2006;Paewai et al 2007). Anderson and Slade (2016) found that pressure from university management increased the likelihood of faculty allocating more time to the pursuit of grants, including what they describe as uninteresting grants that contribute to decreases in work satisfaction. Auranen and Nieminen (2010) suggest that the shift in research funding from institutional-based to competitive grant based system has impacted adversely on faculty research time.…”
Section: Pis Entrepreneurs and The Allocation Of Timementioning
confidence: 99%